Teaching method competencies used by extensionists in transferring the good agricultural practices to Malaysian farmers - Tiraieyari, Neda; Idris, Khairuddin; Hamzah, Azimi; Uli, Jegak (American-Eurasian Network for Scientific Information, 2010)
The purpose of this study is to determine level of teaching method competency and extensionists’ job performance. Furthermore this study aimed to determine relationship between teaching method competencies and extensionists’ job performance in relation to the Good Agricultural Practice (GAP) among Malaysian extensionists at the Department of Agriculture (DOA). This study focused on extensionists transferring the GAP to the farmers using variety of extension teaching methods. The study employed stratified random sampling technique. Samples are chosen with a technique called proportional sample allocation. The sample consisted of 210 extensionists from the Department of Agriculture in four states of Malaysia. The data were analyzed using descriptive statistics and Pearson correlation analysis. Extensiosists reported high level of teaching methods competency and job performance. The findings supported a positive relationship between teaching method competencies and job performance.